2018
DOI: 10.1128/msphere.00147-18
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia chaffeensis TRP75 Interacts with Host Cell Targets Involved in Homeostasis, Cytoskeleton Organization, and Apoptosis Regulation To Promote Infection

Abstract: Human monocytic ehrlichiosis (HME) is caused by an obligatory intracellular bacterium, E. chaffeensis, and is one of the most prevalent, life-threatening emerging infectious zoonoses in the United States. The mechanisms through which E. chaffeensis invades and establishes an intracellular niche are not well understood but are dependent on secreted ehrlichial effector proteins. The significance of this study is in addressing how intracellular pathogens, particularly those with small genomes such as Ehrlichia, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The majority of known ehrlichial immunoreactive proteins, including TRPs, were initially classified as hypothetical proteins. However, our recent studies have revealed the functional aspects of TRPs, and it is now established that they are secreted effectors that interact with an array of host proteins and have various distinct functions during infection [38][39][40][41] . Hypothetical proteins have also been shown to be predominant immunoreactive proteins in other intracellular pathogens, suggesting that many antigenic and potentially protective proteins have unknown function 24,42 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of known ehrlichial immunoreactive proteins, including TRPs, were initially classified as hypothetical proteins. However, our recent studies have revealed the functional aspects of TRPs, and it is now established that they are secreted effectors that interact with an array of host proteins and have various distinct functions during infection [38][39][40][41] . Hypothetical proteins have also been shown to be predominant immunoreactive proteins in other intracellular pathogens, suggesting that many antigenic and potentially protective proteins have unknown function 24,42 .…”
Section: Discussionmentioning
confidence: 99%
“…(34) These receptors could be triggered by Ehrlichia tandem repeat proteins (TRPs), such as TRP75 and TRP120, that are secreted into cytosol and are known to interact with a diverse group of human proteins associated with innate responses, multiple metabolic processes, and signal transduction. (14,35,36) Alternatively, bacterial or mitochondrial DNA can bind to toll-like receptor 9 (TLR9), another upstream receptor that is involved in production of IFN-I cytokines. This possibility is based on our study showing that the TLR9-MYD88 pathway plays a role in inflammasome activation in macrophages and IOE-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…The exact microbial ligand that triggers caspase-11 activation in our model remains elusive. However, Ehrlichia TRPs that are secreted by the type I secretion system (14,35,36) or Ehrlichia translocated factor-2 (Etf-2) that is secreted by the type IV secretion system into cytosol (40) are likely ligands or PAMPs that trigger inflammasome activation. (41,42) Additionally, our data suggest that DAMPs, such as mitochondrial (mt) DAMPs, are potential ligands that mediate canonical and noncanonical inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…E. chaffeensis TRP effectors are secreted by the T1SS and translocate the vacuole membrane by an unknown mechanism to access the host cell. During infection, TRPs interact with a multitude of host proteins and elicit strong protective antibody responses to molecularly defined linear epitopes (99)(100)(101)(102). TRPs are nucleomodulins that translocate to the host cell nucleus through a noncanonical NLS-independent mechanism (79-81).…”
Section: E Chaffeensismentioning
confidence: 99%